2008
DOI: 10.1016/j.jsat.2007.12.008
|View full text |Cite
|
Sign up to set email alerts
|

The economic costs of substance abuse treatment: Updated estimates and cost bands for program assessment and reimbursement

Abstract: Federal, State, and local government agencies require current and accurate cost information for publicly funded substance abuse treatment programs to guide program assessments and reimbursement decisions. The Center for Substance Abuse Treatment (CSAT) published a list of modality-specific cost bands for this purpose in 2002. However, the upper and lower values in these ranges are so wide that they offer little practical guidance for funding agencies. Thus, the dual purpose of this investigation was to assembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
67
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 29 publications
3
67
1
1
Order By: Relevance
“…Health economists estimate that the resource cost of providing an episode of methadone maintenance can range from $1500 to $8000, depending on the length of the episode, while the cost of providing an episode of non-methadone substance use disorder treatment can range from $1000–$5000 (French, Popovici, & Tapsell, 2008). The out-of-pocket cost to patients depends largely on insurance coverage.…”
mentioning
confidence: 99%
“…Health economists estimate that the resource cost of providing an episode of methadone maintenance can range from $1500 to $8000, depending on the length of the episode, while the cost of providing an episode of non-methadone substance use disorder treatment can range from $1000–$5000 (French, Popovici, & Tapsell, 2008). The out-of-pocket cost to patients depends largely on insurance coverage.…”
mentioning
confidence: 99%
“…French et al, (2008) reported the average cost per episode for different SUD treatment modalities as well as cost bands for each estimate (French, Popovici, & Tapsell, 2008). These estimates are based on more than 100 studies that collected primary data on treatment program resources used and associated costs using the Drug Abuse Treatment Cost Analysis Program (DATCAP) (French, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…This can be costly for patients over time (French, Popovici, and Tapsell, 2008). Prior work documents that expenditures are substantially higher among privately-insured, non-elderly adults with SUD diagnoses compared to the same population as a whole (Harwood et al 2017; Friedman et al 2017).…”
Section: Introductionmentioning
confidence: 99%